Modeling of Combipile Application in Soft Soil for Excavation Using PLAXIS 2D - Sulaiman, Shalihen; Yusof, Mohd Fairus (Recent Trends in Civil Engineering and Built Environment, 2021)
Soft soil is one of the most difficult soils to deal with due to its characteristics such as low permeability, low strength, and volume instability. Thus, there is a challenge mainly concentrated on the stability of the soil for the excavation of such construction. A flooding bypass project at Sungai Kesang, Johor faces a problem where the method of excavation that was implemented at soft soil fails in terms of stability. The objective of this study is to produce a combipile model and analyze the stability due to excavation on soft soil. Also, to calculate the required depth of combipile using a manual calculation. The study will mainly be focused on the flooding bypass project at Sungai Kesang, Johor. Thus, two types of combipile which are Single H-King Pile and Double H-King Pile were used in this study. Three models will be used which are Conventional Excavation (Model 1), Single H-King Pile (Model 2), and Double H-King Pile (Model 3). The model which gave the lowest lateral movement is Model 3 with 18 meters combipile. Expectedly from this study, the use of combipiles can reduce the lateral movement of soft soil significantly and a good agreement will be obtained from manual calculation and simulation method.